2022
DOI: 10.1088/1755-1315/985/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Land Suitability Based on Area Functions in the Merawu Watershed, Banjarnegara Regency

Abstract: The decline in the quality of land and the environment is closely related to the increase in changes in land use to settlements as well as to agricultural land that is not in accordance with the spatial layout and function of an area. The purpose of this study is to analyze the suitability of land spatial plans based on the function of the area and analyze the suitability of land use to the function of the area. The method used is the scoring method by assigning a value to the nature of the parameters used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In recent years, numerous studies have been conducted which have successfully examined the removal of heavy metals and organic pollutants that coexist in wastewater. [76][77][78] The selection of an appropriate treatment method depends on a variety of factors, including the economic and environmental impacts associated with the method. Therefore, it is important to carefully evaluate and select the most appropriate combination of removal technologies for each specic situation to achieve efficient and effective removal of heavy metals and organic pollutants from wastewater.…”
Section: Effective Methods For Heavy Metal Remediationmentioning
confidence: 99%
“…In recent years, numerous studies have been conducted which have successfully examined the removal of heavy metals and organic pollutants that coexist in wastewater. [76][77][78] The selection of an appropriate treatment method depends on a variety of factors, including the economic and environmental impacts associated with the method. Therefore, it is important to carefully evaluate and select the most appropriate combination of removal technologies for each specic situation to achieve efficient and effective removal of heavy metals and organic pollutants from wastewater.…”
Section: Effective Methods For Heavy Metal Remediationmentioning
confidence: 99%
“…As such, this present study serves as a reference for further investigations on watershed conservation. According to Funan et al (2022) and Wang et al (2022), the Langsa watershed zoning map is very important as a follow-up to control land suitability for the three zones. Indarto (2020) identified that the importance of the watershed position as a comprehensive planning unit is the basic requirement for maintaining a balance when using forest, land, and water resources.…”
Section: Introductionmentioning
confidence: 99%